Hukum Acara dalam Pengujian Undang-Undang di Indonesia - Ambarsari, Retno (Publikasi Indonesia, 2022)
Indonesia is a state of law. As a state of law, all aspects of social, national and state life, including government, must always be based on law. This study aims to determine the process of testing the Indonesian state law by carrying out procedural law. This research method is normative legal research (library) and sociological legal research (empirical). This journal discusses the procedural process in filing a Judicial Review at the Constitutional Court, including the important stages that must be considered in submitting an application. When viewed from the point of view of the teachings of trias politica, it is in order to provide protection and enforcement of human rights in the context of democracy and democratic law enforcement or a democratic state that has a constitutional basis.